Uncertainty of forecasting (in)solvency of pension system based on NDC model - Chybalski, Filip (Niepewność w prognozowaniu (nie)wypłacalności w systemie emerytalnym opartym na modelu NDC, 2015)
The main purpose of this paper is to identify and characterise the factors of uncertainty in forecasting the (in)solvency of a pension system based on the non-financial defined contribution model (NDC) and to evaluate the forecasting function of automatic balance mechanisms (ABM). The study is theoretical and empirical. It dismisses the hypothesis of automatic balancing of the NDC model, which justifies the forecasting of its (in)solvency. The paper discusses the problem of uncertainty in the long-term forecasting of the (in)solvency of a pension system and shows the rationale of applying ABM. It has an important forecasting function and support a long-term financial balance in the NDC model. The empirical part of the paper discusses, using a case study, the ABM-based principles of indexation in Sweden, considered to be exemplary in literature. They are juxtaposed to the principles of indexation under the Polish 1st pillar functioning without ABM and are detached from the changes in the economic and demographic conditions of the pension system
Ekonometria = Econometrics, 2015, Nr 1 (47), s. 56-67
Keywords: pension; NDC; defined contribution; solvency; automatic balance mechanism; emerytura; zdefiniowana składka; wypłacalność; automatyczny mechanizm bilansujący